Photofield effect and photoresponse properties of the transparent oxide-based BaInZnO thin-film transistors - Kim, Si Joon; Gunduz, Bayram; Yoon, Doo Hyun; Kim, Hyun Jae; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2013)
The photoresponse properties of the BaInZnO (BIZO) thin film transistors were investigated by the output and transfer characteristics. The drain current of the BIZO (10% Ba) and BIZO (20% Ba) transistors in turn-on and turn-off states is significantly increased with light illumination. The photoresponse values of the BIZO (10% Ba) and BIZO (20% Ba) transistors in turn-off and turn-on states were found to be 4.56 and 6.27, respectively, while the photoresponse values of the BIZO (10% Ba) and BIZO (20% Ba) transistors in turn-off and turn-on states were found to be 6.14 and 11.714, respectively. The photoresponse values of the transistors in turn-off state are lower than that of turn-on state. This indicates that the dominant photocurrent mechanism of the BIZO transistors is based on photovoltaic effects. The photoresponse properties of the BIZO transistors were improved with the increasing doping ratio of Ba. The obtained results indicate that BIZO transistors could be used as a photosensor for optoelectronic applications. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Transparent oxide semiconductor; BaInZnO photo-transistor